Matrum: a space for learning, experimenting & sharing around food - Hernández Pacheco, Raquel (My University, 2021)
We live in a globalized world with hyper-connectivity: individuals and communities are more connected than ever before. Food-related issues emerge when discussing about globalization: on the one hand, the global flow of people leads to multiculturalism and the opportunity of sharing food knowledge which previously was kept inside the physical borders. On the other hand, there is the threat of homogenization. New global standards around food are being created, to the detriment of local food cultures and its social structures, which are based on centuries-old place identity. Knowledge about food is disappearing as its production is becoming more and more industrialized. This thesis explores the creation of a platform in the urban context, a Matrum, which stimulates a local food community, giving the tools necessary to engage people to question their beliefs around food, seek knowledge for better food management, and sharing this knowledge with their peers. Its strategy is about connecting the geographical preconditions of a place with the local knowledge of its community, drawing a difference between what traditional and local food knowledge is. The process starts taking references in food culture, both in the Nordic and Mediterranean countries, learning how they relate to place and identity. Parallely, a context study based on site analysis, observation and statistical data is carried out to understand the local community and explore the context-dependent qualities required for such platform to exist. As a result, the Matrum, or “food room”, is a pavilion-like structure in the middle of a park in the neighbourhood of Kvillebäcken in Gothenburg. This room serves as a center of support for activities related to food for the surrounding community, focusing on the local aspect: it has a very close connection to its geographical and social context. As a last step, there is a brief study on a speculative implementation of a network of Matrum on a city scale.
Keywords: Matrum, food culture, local, eating, cooking, farming, community